Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Age and spatial distribution of the world's oldest trees - Jiajia Liu; Shangwen Xia; Di Zeng; Cong Liu; Yingjun Li; Wenjing Yang; Bao Yang; Jian Zhang; Ferry Slik; David B. Lindenmayer (Conservation Biology, 2022)
Extremely old trees have important roles in providing insights about historical climatic events and supporting cultural values, yet there has been limited work on their global distribution and conservation. We extracted information on 197,855 tree cores from 4854 sites and combined it with other tree age (e.g., the OLDLIST) data from a further 156 sites to determine the age of the world's oldest trees and quantify the factors influencing their global distribution. We found that extremely old trees >1000 years were rare. Among 30 individual trees that exceeded 2000 years old, 27 occurred in high mountains. We modeled maximum tree age with climatic, soil topographic, and anthropogenic variables, and our regression models demonstrated that elevation, human population density, soil carbon content, and mean annual temperature were key determinants of the distribution of the world's oldest trees. Specifically, our model predicted that many of the oldest trees will occur in high‐elevation, cold, and arid mountains with limited human disturbance. This pattern was markedly different from that of the tallest trees, which were more likely to occur in relatively more mesic and productive locations. Global warming and expansion of human activities may induce rapid population declines of extremely old trees. New strategies, including targeted establishment of conservation reserves in remote regions, especially those in western parts of China and the United States, are required to protect these trees.

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

Preserving 40% forest cover is a valuable and well‐supported conservation guideline: reply to Banks‐Leite et al - Víctor Arroyo‐Rodríguez; Lenore Fahrig; James I. Watling; Justin Nowakowski; Marcelo Tabarelli; Lutz Tischendorf; Felipe P. L. Melo; Bráulio A. Santos; Maíra Benchimol; Jose Carlos Morante‐Filho; J. W. Ferry Slik; Ima C. G. Vieira; et al. (Ecology Letters, 2021)
Banks‐Leite et al . (2021) claim that our suggestion of preserving ≥ 40% forest cover lacks evidence and can be problematic. We find these claims unfounded, and discuss why conservation planning urgently requires valuable, well‐supported and feasible general guidelines like the 40% criterion. Using region‐specific thresholds worldwide is unfeasible and potentially harmful.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Designing optimal human‐modified landscapes for forest biodiversity conservation - Víctor Arroyo‐Rodríguez; Lenore Fahrig; Marcelo Tabarelli; James I. Watling; Lutz Tischendorf; Maíra Benchimol; Eliana Cazetta; Deborah Faria; Inara R. Leal; Felipe P. L. Melo; Jose C. Morante‐Filho; Bráulio A. Santos; et al. (Ecology Letters, 2020)
Agriculture and development transform forest ecosystems to human‐modified landscapes. Decades of research in ecology have generated myriad concepts for the appropriate management of these landscapes. Yet, these concepts are often contradictory and apply at different spatial scales, making the design of biodiversity‐friendly landscapes challenging. Here, we combine concepts with empirical support to design optimal landscape scenarios for forest‐dwelling species. The supported concepts indicate that appropriately sized landscapes should contain ≥ 40% forest cover, although higher percentages are likely needed in the tropics. Forest cover should be configured with c . 10% in a very large forest patch, and the remaining 30% in many evenly dispersed smaller patches and semi‐natural treed elements (e.g. vegetation corridors). Importantly, the patches should be embedded in a high‐quality matrix. The proposed landscape scenarios represent an optimal compromise between delivery of goods and services to humans and preserving most forest wildlife, and can therefore guide forest preservation and restoration strategies.

Soil niche of rain forest plant lineages: Implications for dominance on a global scale - Şerban Procheş; Rahayu S. Sukri; Salwana M. Jaafar; Erwin J.J. Sieben; Nurul Hazlina Zaini; Norain Abas; Siti Nurqayah Suhaini; Nurul Maz Juhairah Manjul; Muhammad Abdul Hakeem Julaihi; David J. Marshall; J.W. Ferry Slik; Desika Moodley (Journal of Biogeography, 2019)
Aim Why some lineages are species‐rich and widespread, while others are species‐poor and localized, is a fundamental question in evolutionary biology and ecology. Diversification and range expansion relate to lineage‐specific niche characters, but this link has seldom been quantified across multiple lineages and environments. This study explored the link between local dominance and soil niche in rain forest plants, and tested the hypothesis that local soil niche patterns can be used to predict the global diversity and occupancy of equal‐aged plant lineages. Location The study was carried out in Brunei Darussalam (Borneo) and projected worldwide. Methods Our approach involved the subdivision of vascular plants into the lineages found 120 Mya, a time preceding the explosive radiation of the eudicots. We quantified the representation of the 120 Mya lineages in different forest types associated with dramatically different soils, but sharing the same climatic conditions. The forest types included primary and secondary lowland rain forest, flooded and nutrient‐impoverished inland forests, and mangroves. Niche breadth and position, estimated from the soil types that a lineage occupied, were used to predict global diversity and occupancy patterns, after accounting for relatedness to the dominant eudicots. Results Despite marked differences in soil characteristics among the forest types, three eudicot lineages (Malvidae, Fabidae, Asteridae) were consistently dominant over the other 28 lineages present. A broad, intermediate soil niche, relatedness to eudicots, and the interaction between these factors were found to be strong predictors of global diversity and occupancy. Main conclusions We show that vegetation plot data from one of the world's most diverse regions (in terms of plant species richness and ancient lineage representation) can be used to successfully predict lineage diversity and occupancy on a global scale. However, because lineage dominance likely depends on the interaction between soil niche and above‐ground factors, including above‐ground niche features should improve the accuracy of predicting global distribution and diversity—particularly when explaining eudicot dominance.

The distribution of plants and seed dispersers in response to habitat fragmentation in an artificial island archipelago - Jiajia Liu; Ferry Slik; David A. Coomes; Richard T. Corlett; Yanping Wang; Maxwell Wilson; Guang Hu; Ping Ding; Mingjian Yu (Journal of Biogeography, 2019)
Aim Small, old‐growth forest fragments generally have more small‐seeded plants than large patches, due to the disappearance of large seed dispersing vertebrates. This pattern may differ for secondary forest fragments where differential migration ability rather than persistence of seed dispersers may be driving plant community assembly. In this study, we investigated the effect of habitat fragmentation on seed dispersers and plant community structure in regenerating forests. Location The Thousand Island Lake, China. Taxon Plants, birds and mammals. Methods We compiled diversity and abundance data for birds and mammals on islands in the Thousand Island Lake, China. We also surveyed the secondary plant communities and measured seed dispersal traits. Results Community‐weighted mean seed size of woody plants decreased with island size. This pattern was related to compositional difference of the dispersers. We found that mammal diversity and abundance was only weakly or not related to island size; whereas bird diversity and abundance increased strongly with island size. Density of bird‐dispersed plants was significantly positively related with island size. Since birds tend to disperse smaller seeds than mammals, the trend in seed size may have been a consequence of the shift in relative abundance of the two disperser guilds. Main Conclusions Differential responses of seed dispersers to habitat fragmentation may lead to pervasive shifts in the plant community structure of regenerating forest fragments. Our study highlights the importance of keeping large continuous forests in order to retain mammals and their dispersal capabilities.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Temporal Changes in Tree Species and Trait Composition in a Cyclone-prone Pacific Dipterocarp Forest - Carla C. Monoy; Kyle W. Tomlinson; Yoshiko Iida; Nathan G. Swenson; J. W. Ferry Slik (Ecosystems, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Phylogeography of three closely related myrmecophytic pioneer tree species in SE Asia: implications for species delimitation - Brigitte Fiala; Ferry Slik; Kurt Weising; Ulrich Maschwitz; Maryati Mohamed; Jamsari; Daniela Guicking (Organisms Diversity & Evolution, 2016)

Spatial patterns and environmental correlates of bryophyte richness: sampling effort matters - Shengbin Chen; J. W. Ferry Slik; Lingfeng Mao; Jian Zhang; Rula Sa; Kexin Zhou; Jixi Gao (Biodiversity and Conservation, 2015)

Large trees drive forest aboveground biomass variation in moist lowland forests across the tropics - J. W. Ferry Slik; Gary Paoli; Krista McGuire; Ieda Amaral; Jorcely Barroso; Meredith Bastian; Lilian Blanc; Frans Bongers; Patrick Boundja; Connie Clark; Murray Collins; Gilles Dauby; et al. (Global Ecology and Biogeography, 2013)
Aim Large trees (d.b.h. ≥ 70 cm) store large amounts of biomass. Several studies suggest that large trees may be vulnerable to changing climate, potentially leading to declining forest biomass storage. Here we determine the importance of large trees for tropical forest biomass storage and explore which intrinsic (species trait) and extrinsic (environment) variables are associated with the density of large trees and forest biomass at continental and pan‐tropical scales. Location Pan‐tropical. Methods Aboveground biomass ( AGB) was calculated for 120 intact lowland moist forest locations. Linear regression was used to calculate variation in AGB explained by the density of large trees. Akaike information criterion weights ( AICc ‐wi) were used to calculate averaged correlation coefficients for all possible multiple regression models between AGB /density of large trees and environmental and species trait variables correcting for spatial autocorrelation. Results Density of large trees explained c . 70% of the variation in pan‐tropical AGB and was also responsible for significantly lower AGB in Neotropical [287.8 (mean) ± 105.0 ( SD ) M g ha −1 ] versus Palaeotropical forests (Africa 418.3 ± 91.8 M g ha −1 ; Asia 393.3 ± 109.3 M g ha −1 ). Pan‐tropical variation in density of large trees and AGB was associated with soil coarseness (negative), soil fertility (positive), community wood density (positive) and dominance of wind dispersed species (positive), temperature in the coldest month (negative), temperature in the warmest month (negative) and rainfall in the wettest month (positive), but results were not always consistent among continents. Main conclusions Density of large trees and AGB were significantly associated with climatic variables, indicating that climate change will affect tropical forest biomass storage. Species trait composition will interact with these future biomass changes as they are also affected by a warmer climate. Given the importance of large trees for variation in AGB across the tropics, and their sensitivity to climate change, we emphasize the need for in‐depth analyses of the community dynamics of large trees.

Consequences of defaunation for a tropical tree community - Rhett D Harrison; Sylvester Tan; Joshua B. Plotkin; Ferry Slik; Matteo Detto; Tania Brenes; Akira Itoh; Stuart J. Davies (Ecology Letters, 2013)
Hunting affects a considerably greater area of the tropical forest biome than deforestation and logging combined. Often even large remote protected areas are depleted of a substantial proportion of their vertebrate fauna. However, understanding of the long‐term ecological consequences of defaunation in tropical forests remains poor. Using tree census data from a large‐scale plot monitored over a 15‐year period since the approximate onset of intense hunting, we provide a comprehensive assessment of the immediate consequences of defaunation for a tropical tree community. Our data strongly suggest that over‐hunting has engendered pervasive changes in tree population spatial structure and dynamics, leading to a consistent decline in local tree diversity over time. However, we do not find any support for suggestions that over‐hunting reduces above‐ground biomass or biomass accumulation rate in this forest. To maintain critical ecosystem processes in tropical forests increased efforts are required to protect and restore wildlife populations.

Leaf element concentrations of terrestrial plants across China are influenced by taxonomy and the environment - Shi‐Bao Zhang; Jiao‐Lin Zhang; J. W. Ferry Slik; Kun‐Fang Cao (Global Ecology and Biogeography, 2012)
Aim The productivity, functioning and biogeochemical cycles of terrestrial ecosystems are strongly affected by leaf element concentrations. Understanding the biological and ecological factors affecting leaf element concentrations is therefore important for modelling the productivity and nutrient fluxes of ecosystems and their responses to global change. The present study aimed to determine how leaf element concentrations are linked to taxonomy and the environment. Location China. Methods The concentrations of 10 leaf elements of 702 terrestrial plant species from different biomes were extracted from publications. The links between environmental variables, taxonomy and leaf elements were analyzed using phylogenetically comparative methods and partial Mantel tests. Results Taxonomy had stronger effects on leaf S and SiO 2 than latitude, explaining 40.2–43.9% of total variation, whereas latitude had stronger effects on leaf N, P, K, Fe, Al, Mn, Na and Ca concentrations, explaining 19.5–52.1% of total variation. Leaf N, S, Al, Fe and Na concentrations were correlated with mean annual precipitation (MAP), while leaf N, P and Fe concentrations were correlated with mean annual temperature (MAT). Latitude, MAP and MAT were significantly correlated with the first axis of a principal components analysis (PCA). This first axis was associated with leaf elements involved in protein synthesis and photosynthesis. The other PCA axes, which were not correlated with MAT, latitude and MAP, were associated with leaf elements responsible for cell structure and enzymes. Main conclusions Leaf element concentrations of terrestrial plants in China were correlated with climate, latitude and taxonomy. With the exception of S and SiO 2 , the environmental factors were more important in explaining leaf element variation than taxonomy. Therefore, changes in temperature and precipitation will directly affect the spatial patterns of leaf elements and thus the associated nutrient fluxes and ecosystem functioning.

Erratum to: Comparative chloroplast DNA phylogeography of two tropical pioneer trees, Macaranga gigantea and Macaranga pearsonii (Euphorbiaceae) - Daniela Guicking; Brigitte Fiala; Frank R. Blattner; Ferry Slik; Maryati Mohamed; Kurt Weising (Tree Genetics & Genomes, 2011)

Comparative chloroplast DNA phylogeography of two tropical pioneer trees, Macaranga gigantea and Macaranga pearsonii (Euphorbiaceae) - Daniela Guicking; Brigitte Fiala; Frank R. Blattner; Ferry Slik; Maryati Mohamed; Kurt Weising (Tree Genetics & Genomes, 2011)

Fire as a selective force in a Bornean tropical everwet forest - J. W. Ferry Slik; Floris C. Breman; Caroline Bernard; Marloes van Beek; Charles H. Cannon; Karl A. O. Eichhorn; Kade Sidiyasa (Oecologia, 2010)

Biodiversity inventory and informatics in Southeast Asia - Campbell O. Webb; J. W. Ferry Slik; Teguh Triono (Biodiversity and Conservation, 2010)

Tree diversity, composition, forest structure and aboveground biomass dynamics after single and repeated fire in a Bornean rain forest - J. W. Ferry Slik; Caroline S. Bernard; Marloes Van Beek; Floris C. Breman; Karl A. O. Eichhorn (Oecologia, 2008)

Wood Density as a Conservation Tool: Quantification of Disturbance and Identification of Conservation‐Priority Areas in Tropical Forests - J. W. FERRY SLIK; CAROLINE S. BERNARD; FLORIS C. BREMAN; MARLOES VAN BEEK; AGUS SALIM; DOUGLAS SHEIL (Conservation Biology, 2008)
Inventories of tree species are often conducted to guide conservation efforts in tropical forests. Such surveys are time consuming, demanding of expertise, and expensive to perform and interpret. Approaches to make survey efforts simpler or more effective would be valuable. In particular, it would be good to be able to easily identify areas of old‐growth forest. The average density of the wood of a tree species is closely linked to its successional status. We used tree inventory data from eastern Borneo to determine whether wood density can be used to quantify forest disturbance and conservation importance. The average density of wood in a plot was significantly and negatively related to disturbance levels, with plots with higher wood densities occurring almost exclusively in old‐growth forests. Average wood density was unimodally related to the diversity of tree species, indicating that the average wood density in a plot might be a better indicator of old‐growth forest than species diversity. In addition, Borneo endemics had significantly heavier wood than species that are common throughout the Malesian region, and they were more common in plots with higher average wood density. We concluded that wood density at the plot level could be a powerful tool for identifying areas of conservation priority in the tropical rain forests of Southeast Asia.

Effects of fire and selective logging on the tree species composition of lowland dipterocarp forest in East Kalimantan, Indonesia - J.W. Ferry Slik; Rene W. Verburg; Paul J.A Keßler (Biodiversity and Conservation, 2002)